State-dependent learned valuation drives choice in an invertebrate. - Pompilio, L; Kacelnik, A; Behmer, S (2006)
Humans and other vertebrates occasionally show a preference for items remembered to be costly or experienced when the subject was in a poor condition (this is known as a sunk-costs fallacy or state-dependent valuation). Whether these mechanisms shared across vertebrates are the result of convergence toward an adaptive solution or evolutionary relicts reflecting common ancestral traits is unknown. Here we show that state-dependent valuation also occurs in an invertebrate, the desert locust Schistocerca gregaria (Orthoptera: Acrididae). Given the latter's phylogenetic and neurobiological distance from those groups in which the phenomenon was already known, we suggest that state-dependent valuation mechanisms are probably ecologically rational solutions to widespread problems of choice.